Characterization of New Regulatory Mutants of Bacteriophage T4 - Johnson, James R. (1974)
Plating techniques which eliminate T4 plaque formation on Escherichia coli by folate analogue inhibition of dihydrofolate (FH(2)) reductase (EC 1.5.1.3) allowed the isolation of folate analogue-resistant (far) mutants of T4. One class of far mutants overproduces the phage-induced FH(2) reductase. Deoxycytidylate deaminase (EC 3.5.4.12), thymidine kinase (EC 2.7.1.21), and deoxycytidine triphosphatase (EC 3.6.1.12) are also overproduced by 20 min after infection at 37 C. The overproduction of FH(2) reductase by these far mutants is not affected by the absence of DNA synthesis. Other types of mutations that affect the synthesis of early enzymes cause overproduction in the absence of DNA synthesis of some of the above enzymes but not of FH(2) reductase. Therefore, overproducing far mutants apparently have mutations in previously undescribed genes controlling the expression of the T4 genome. Three of four mutants under study map near gene 56, and one maps near gene 52. All of these mutants show delays in DNA synthesis, phage production, and lysis and appear to show decreased levels of RNA synthesis based on the cumulative incorporation of uridine.